The gig economy / Alex De Ruyter and Martyn Brown. - Ruyter, Alex de; Brown, Martyn (Martyn David) (Economy, key ideas., 2023)
Alex de Ruyter and Martyn Brown explain the key facets of the gig economy and explore the dangers and potential it affords. Drawing on recent case-studies from the UK, Europe and the USA, it offers an authoritative guide through the theories and issues that surround the gig economy and the ramifications of an increasingly insecure workforce.